General decay for a viscoelastic-type Timoshenko system with thermoelasticity of type III. Issue 3 (11th February 2023) - Fayssal, Djellali; Soraya, Labidi; Frekh, Taallah
Abstract : We consider a one-dimensional thermoelastic Timoshenko system, where the heat conduction is given by Green and Naghdi theories and acting on shear force. We prove that the unique damping given by the memory is sufficiently strong to stabilize the system exponentially, depending on a new relationship between the coefficients of the system and under some assumptions on the kernel of the memory term. In fact, we establish a general decay result, of which exponential and polynomial decay results are special cases.